Corporate Social Responsibility Reporting, Intellectual Capital, and Financial Performance of Listed Firms in Ghana - Tetteh, Anthony Buawolor; Awartey, Sophia; Mawutor, John Kwaku Mensah; Aveh, Felix Kwame; Antwi, Samuel; Ofoeda, Isaac (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
This study examines the moderating effect of intellectual capital (IC) on the relationship between corporate social responsibility (CSR) reporting and financial performance of 36 listed firms in Ghana from 2013 to 2022. We employed the system generalized method of moment and the dynamic panel threshold regression. We used data from BankScope, the Refinitiv database, and unconsolidated financial statements. We discovered a significant negative effect of CSR reporting on financial performance. Conversely, the IC components including value-added intellectual coefficient (VAIC), human capital efficiency (HCE), and structural capital efficiency (SCE) have a positive effect on financial performance. However, capital employed efficiency (CEE) negatively impacts financial performance of listed firms in Ghana. Our study further revealed that VAIC, HCE, and SCE exhibit positive and statistically significant moderating effects on the relationship between CSR reporting and financial performance. Our analysis also reported a negative and significant effect of CEE on the relationship between CSR reporting and financial performance. We also found that CSR reporting positively affects financial performance of listed firms in Ghana when IC (VAIC, HCE, and SCE) exceeds a certain threshold. Firms must carefully consider the interplay between CSR reporting, IC, and environmental engagement to optimize their financial performance. This research contributes to the theoretical understanding by demonstrating how IC components, particularly VAIC, HCE, and SCE, positively moderate the relationship between CSR reporting and financial performance, offering fresh perspectives on the role of IC in enhancing the financial outcomes of CSR activities among listed firms in Ghana.